Embracing Adult Learners through Storytelling: Community Empowerment in Temajuk Tourism Village - Mutiaraningrum, Ira; Meniwati, Meniwati (Budapest International Research and Critics University, 2021)
Quality human recourse is the determinant factor for the improvement of coastal-border areas. The Indonesian government encourages the improvement of foreign since foreign language is indispensable for competing in the global economy. The Ministry of Tourism and Creative Economy simultaneously holds English language training in tourism destinations in Indonesia, including the Temajuk Village that borders directly with Malaysia. This one group pretest-posttest design experimental study tested the effectiveness of a traditional yet powerful, storytelling, in improving the English speaking skill of the Tour guides in Temajuk Tourism Village. The study has proven that storytelling significantly improved participants’ English speaking skills with a significance value of 0.045 (< 0.05). In terms of aspects of speaking skills, it was found that participants’ Volume (0.038 < 0.05), Facial Expression (0.045 < 0.05), and Action-body Language (0.009 < 0.05) improved significantly. Meanwhile, storytelling had no significant effect of participants’ Eye contact (0.815 > 0.05) and Content of the story (0.552 > 0.05). This study pertains to showing precious insight into community-based engagement practice. It proffers that storytelling can support tour guides’ English speaking skills and potentially help the community’s economy as part of community empowerment.